Hate speech detection using machine learning techniques - Manzoor, Tahbib; Araf, Md. Wahidur Rahman; Omi, Monjurul Sharker; Abir, Arpan Das; Abir, Tanvir Ahmed (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.